Analytic Visibility on the GPU. (6th May 2013) - Auzinger, T.; Wimmer, M.; Jescke, S.
Abstract: This paper presents a parallel, implementation‐friendly analytic visibility method for triangular meshes. Together with an analytic filter convolution, it allows for a fully analytic solution to anti‐aliased 3D mesh rendering on parallel hardware. Building on recent works in computational geometry, we present a new edge‐triangle intersection algorithm and a novel method to complete the boundaries of all visible triangle regions after a hidden line elimination step. All stages of the method are embarrassingly parallel and easily implementable on parallel hardware. A GPU implementation is discussed and performance characteristics of the method are shown and compared to traditional sampling‐based rendering methods.